*El desarrollo de una cultura de la evaluación - Murphy, Dermot; Frodden Armstrong (TRADUCTORA), María Cristina (Íkala, Revista de Lenguaje y Cultura, 2002)
This article presents a variety of arguments in favor of a culture of participatory and effective evaluation, especially in educational institutions. It states how important it is for all members of the organization to use evaluation, to be able to discuss its findings, and to participate in decision making and in the implementation of the changes planned, so that the evaluation can support change and development. Personal, professional and institutional benefits and some strategic guidelines for the development of a culture of participatory and effective evaluation are also mentioned.